Impacts of climatic variables on cyclone in the coastal regions of Bangladesh (Progressive Agriculture, 2016)
Geographical position of Bangladesh makes it vulnerable to several extreme weather events like cyclone in the southern part due to extreme climatological events. Therefore, in this study, we had mainly tried to study on the variations of temperature, relative humidity (RH) and sunshine hours (SH) in the coastal areas to find out its effect on the formation of cyclone. Data from 1975-2014 of these climatic variables was provided by the Bangladesh Meteorological Department (BMD) and analyzed with the statistical tool MS Excel 2010 as per objective of the study. Results showed that in the16 stations, temperature has shown homogenous trend where it has seen that in all the stations the Tmean and Tmax were ranging from 180C to 300C and 280C to 420C respectively. In maximum stations, the Tmax and extreme Tmean has found in the months of April and May which is a cyclone occurring month. Again RHmax has mostly found in the post monsoon season where RHmean is ranging 84~88% mainly in the Khulna, Mongla, Khepupara and Barisal areas, may have profound influence on the formation of cyclone especially in this area. SHmax has found in the month April where the highest was about 12.08 hr. These higher amounts of temperature play profound influence in increasing temperature in the studied areas which have direct consequences on cyclone events. So, extreme temperature, RH and SH in these months may had profound influence on the formation of cyclone. These information could be very useful to the related scientists to study on several extreme weather events due to variation of temperature especially on cyclogenesis which are a most common devastating phenomenon for the coastal areas like Bangladesh.Progressive Agriculture 27 (3): 272-284, 2016